Upward Planar Drawings and Switch-regularity Heuristics - Didimo, Walter (Journal of Graph Algorithms and Applications, 2006)
In this paper we present a new characterization of switch-regular upward embeddings, a concept introduced by Di Battista and Liotta in 1998. This characterization allows us to define a new efficient algorithm for computing upward planar drawings of embedded planar digraphs. If compared with a popular approach described by Bertolazzi, Di Battista, Liotta, and Mannino, our algorithm computes drawings that are significantly better in terms of total edge length and aspect ratio, especially for low-density digraphs. Also, we experimentally prove that the running time of the drawing process is reduced in most cases. <!—->